Trpm4 Inhibition Slows Neuritogenesis Progression of Cortical Neurons - Leiva-Salcedo, D; Riquelme-Pacheco, D; Juanchuto-Viertel, N (BioMed Central Ltd, 2024)
TRPM4 is a non-selective cation channel activated by intracellular Ca2+ but only permeable to monovalent cations, its activation regulates membrane potential and intracellular calcium. This channel participates in the migration and adhesion of non-excitable cells and forms an integral part of the focal adhesion complex. In neurons, TRPM4 expression starts before birth and its function at this stage is not clear, but it may function in processes such as neurite development. Here we investigate the role of TRPM4 in neuritogenesis. We found that neurons at DIV 0 express TRPM4, the inhibition of TRPM4 using 9-Ph reduces neurite number and slows the progression of neurite development, keeping neurons in stage 1. The genetic suppression of TRPM4 using an shRNA at later stages (DIV2) reduces neurite length. Conversely, at DIV 0, TRPM4 inhibition augments the Cch-induced Ca2 +i increase, altering the calcium homeostasis. Together, these results show that TRPM4 participates in progression of neurite development and suggest a critical role of the calcium modulation during this stage of neuronal development. © The Author(s) 2024.